The influence of Y contribution on crystallographic, topographic and optical properties of ZnO: A heterojunction diode application. (October 2015) - Turgut, G.; Duman, S.; Keskenler, E.F.
Graphical abstract: Highlights: Y doped ZnO thin films were deposited by sol–gel spin coating. Influence of Y contribution on features of ZnO was investigated. The heterojunction diode application was made for YZO samples. The heterojunction structures showed rectification behavior. Abstract: Pure and yttrium (Y) doped ZnO samples were fabricated on micro slide glasses and p-Si wafers for device application via a simple and cheap sol–gel route using a spin coater. The characterization results of XRD, SEM and UV/VIS spectrophotometer revealed the films to have nano-sized ZnO hexagonal wurtzite structures with (0 0 2) preferential orientation and optical band gap values depending on Y doping ratio. The optical band of 3.285 eV for pure ZnO initially increased to 3.305 eV, 3.332 eV and 3.341 eV for 1 at.%, 2 at.% and 3 at.% Y incorporated ZnO films and then decreased to 3.271 eV and 3.258 eV for 5 at.% and 7 at.% Y contents. The electrical features of Al/ZnO:Y/p-Si/Al heterojunction structures were tested by I – V measurements. The heterojunction structures showed a rectifying behavior under dark condition. The Φ b and n values for the devices were identified by using I – V measurements. It was observed that the rectification ratio value of 3 × 10 4 calculated at +3.0 V for Al/ZnO:Y/p-Si (5 at.% Y doped ZnO) heterojunction structure was higher than most of n-ZnO/p-Si heterojunction devices reported in the literature.